Effect of Moringa Leaf Meal Supplementation on Haematological and Serum Biochemical Profile of Broiler Chicken - Lateef, Tijani; Adetayo, Akanji; Kudirat, Agbalaya; Murisiku, Onigemo (Indian Journal of Animal Nutrition, 2018)
The aim of this study was to evaluate the effects of feeding Moringa oleifera leaf meal (MOLM) on the haematological and serum biochemical profile of broiler chicken. A total of two hundred broiler unsexed chickens (Anak strain) were randomly allotted to five treatments. Each treatment onsisted of forty birds in five replicates. Shade dried MOLM was incorporated into the broiler starter and finisher diets at 0, 5, 10, 15 and 20% levels, respectively. The contents of tannin, phytic acid, saponin and oxalate were higher in the MOLM than fresh moringa leaves (FML). Dietary level of MOLM showed negative correlation with packed cell volume and haemoglobin and values were reported lowest in 20% MOLM fed birds. However, white blood cell and neutrophil counts were found significantly (P<0.05) higher in 15% MOLM incorporated group. Mean corpuscular volume and mean corpuscular haemoglobin was significantly (P<0.05) higher in birds fed 10 and 15% MOLM diets compared to control, 5 and 20% MOLM group. Plasma total protein and albumin concentration was greater in control followed by 5, 10 and 15% MOLM fed birds while lowest (P<0.05) in those fed 20% MOLM. Birds fed on 20% MOLM diet had significantly (P<0.05) higher uric acid concentration. Treatments showed negative correlation with AST and ALT activity and positive correlation with serum creatinine level. Inclusion of different levels of MOLM in the diet of birds did not exert any effect on red blood cell and monocyte count. In conclusion, MOLM could be incorporated into broiler diets up to 15% level without adverse effects on the haematological and serum biochemical indices.